Memaknai Ulang Konsep Pendidikan Islam (Telaah Kritis Epistemologi Hasan Langgulung dalam Pembelajaran di Masa Pandemi Covid-19) - Sari, Ima Frafika; Supriatna, Ucup; Ma'rufah, Afni (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to reinterpret the epistemology of Hasan Langgulung Islamic education and its application in learning during the Covid-19 pandemic. As a library research, the primary research data are in the form of six writings by Hasan Langgulung. The researcher also presented research data related to learning that had occurred during the COVID-19 pandemic season. The data collection technique is done by documentation. Then the data analysis was done descriptively-analytically. Researchers generalized and critically analyzed the concept of Hasan Langgulung Islamic education from various primary and secondary literatures and then discussed the concept on the actualization of Islamic education during the Covid-19 pandemic season. The results of data analysis, in this case Hasan Langgulung's Islamic educational thought paradigm, were then concluded and became the results of research. The results of the study show that online learning that has occurred during the pandemic so far is still disoriented to the epistemology of Islamic education. Hasan Langgulung offers an epistemological paradigm of Islamic education, namely 1) teachers should formulate online learning aims and goals that are realistic and can be measured through indicators with specified timelines. Aims and learning goals are oriented to three aspects of cognitive, affective, and psychomotor; 2) choosing learning strategies to be more precise with guidance, counseling, and providing incidental student assistance; 3) the learning evaluation system must be realistic and measurable, all of which include cognitive, affective, and psychomotor aspects.